Novel pharmaceutical cocrystal of apalutamide, a nonsteroidal antiandrogen drug: synthesis, crystal structure, dissolution, stress, and excipient compatibility - Saladi, Venkata Narasayya; Kammari, Bal Raju; Mandad, Pratap Reddy; Krishna, Gamidi Rama; Sajja, Eswaraiah; Thirumali, Rajan S.; Marutapilli, Arthanareeswari; Mathad, Vijayavitthal T. (Crystal Growth & Design, 2022)
Apalutamide (APA), a second-generation nonsteroidal antiandrogen BCS Class II drug with poor solubility and high permeability. A novel 1:1 cocrystal of Apalutamide (APA) with methylparaben (MP) was identified by cooling crystallization during the cocrystal screening and characterized by various solid-state techniques, such as PXRD, DSC, TGA, FT-IR, and 13C solid-state CP-MAS NMR spectroscopy. The crystal structures of APA and its cocrystal (APA-MP) were determined by the SC-XRD technique. The crystal structure analysis of the APA-MP cocrystal revealed that the APA and MP molecules are connected through strong O–H···O hydrogen bonds. The novel cocrystal improves the solubility and dissolution rate in different physiological conditions compared to poorly soluble APA due to strong hydrogen bond between the drug and the coformer. The cocrystal is stable (physically and chemically) under stress conditions, such as exposure to the relative humidity, mechanical grinding, open exposure to atmosphere at cRT (critical room temperature) and compression pressure of 10 tons. In addition, the compatibility of the cocrystal with excipients used in the drug product of APA (ERLEADA) was also investigated, and no disproportionation of cocrystal was observed.